Effect of Recombinant Interleukin-2 on Cell Mediated Immunity of Chickens Vaccinated against Newcastle Disease - Pralhad, Shambulingappa B.E*, Padalkar R.D. and (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: EN-US; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">A study was conducted on 120 chickens to investigate the effect of Recombinant Interleukin-2 on cell mediated immunity of NDV vaccinated poultry birds. The results of the analysis revealed a useful insight in to the immunomodulatory role of Recombinant IL-2 on cell mediated immune response in poultry birds with significant level of percentage of MI (up to 65.34%) and maximum reaction of DNCB (0.346 mm) in 48 hrs in chickens treated with Rec IL-2 and ND vaccine, when compared to non-vaccinated chickens without IL-2 therapy.